4(5x-2)=2(4x+3)

Simple and best practice solution for 4(5x-2)=2(4x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(5x-2)=2(4x+3) equation:



4(5x-2)=2(4x+3)
We move all terms to the left:
4(5x-2)-(2(4x+3))=0
We multiply parentheses
20x-(2(4x+3))-8=0
We calculate terms in parentheses: -(2(4x+3)), so:
2(4x+3)
We multiply parentheses
8x+6
Back to the equation:
-(8x+6)
We get rid of parentheses
20x-8x-6-8=0
We add all the numbers together, and all the variables
12x-14=0
We move all terms containing x to the left, all other terms to the right
12x=14
x=14/12
x=1+1/6

See similar equations:

| 5/9(26-32)=c | | x-2/5x=510 | | 4(x+3)-(-2x+12)=0 | | -5(2t+9)=-105 | | 8•x-24=0 | | 4y–12=28 | | 3=r-r-4r+2r+3r+6r | | 2(x-1)-3(5x-6)=250 | | (n+6)(n-5)=102 | | 10x-18=5x+7 | | 7x–2=54 | | 9x-17=8x-7 | | 10x-43=4x-7 | | y/16=0.2 | | 14x+10=22 | | 4z/10+6=7 | | 10x-27=2x-3 | | 6x-7=6x+4 | | 3b+4b=6b+16 | | 5m+37=12 | | 4(3w+10)/5=-7 | | 23=4c-9 | | 3x+7=2(2x-0.5) | | 6(x-2)=33+3x | | 4(x+1)=6(2x+6) | | 2x−3=-1 | | 4x+6=1+14x | | 2x−3=1 | | 2^(2x)-10*2^x+16=0 | | 15-5x=6-8 | | 9x-11=3x+10 | | 7/x−5=6 |

Equations solver categories